The Hero Archetype Analysis of Main Character in A Study in Scarlet - santi afrida rahmawati; Yulis Setyowati; Surya Priyambudi (EL2J (English Language and Literature Journal), 2024)
This research aims to analyze hero archetype of main character in A Study in Scarlet. This study explains the hero archetype of main character in A Study in Scarlet. The researcher uses a qualitative approach as a research method. The data source is A Study in Scarlet. Data collection by: (1) read comprehensively the novel (2) Collect and retrieve data from the novel relating to the research problem (3) Fragmenting dialogue in the novel according to the research problem (4) selecting the dialog that are the hero archetype. Meanwhile, the data analysis procedures are: (1) Selecting dialogs in the novel A study in Scarlet, (2) classifying the hero archetype based on objects of Carol Pearson's theory, such as the innocent, the warrior, the caregiver. (4) drawing a conclusion. This study shows that the appearance of the hero archetype in the main character there found A Study in Scarlet. The research delves into the profound exploration of the hero archetype as exemplified by the main character in Arthur Conan Doyle's "A Study in Scarlet." Adopting a qualitative research methodology, this study meticulously dissects the character's traits and actions, primarily drawing from the narrative structure and dialogues within the novel. The principal data source for this research is the text of "A Study in Scarlet." The data collection process was methodical and comprehensive. It began with an in-depth reading of the novel, followed by the extraction of relevant data that directly addresses the research problem. Subsequently, dialogues were fragmented, and a careful selection process was employed to pinpoint those that truly represent the hero archetype. For the analysis, the study employed a systematic procedure. Dialogues from "A Study in Scarlet" were selected and classified based on Carol Pearson's renowned theory of hero archetypes. Pearson's theory delineates various hero archetypes, such as the innocent, the warrior, and the caregiver, each representing different facets of heroism. The findings from this research reveal that the main character in "A Study in Scarlet" resonates with several of these archetypes, showcasing the multidimensionality of his character. In conclusion, this research not only highlights the literary depth and intricacy of Doyle's work but also sheds light on the timeless and universal nature of hero archetypes in classic literature.